PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TEBAK PELAJARAN TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS X SMAN 1 TUALANG KECAMATAN TUALANG KABUPATEN SIAK - Valdi Mensi; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low motivation to learn PPKn class X students at SMAN 1 Tualang, Tualang District, Siak Regency. The formulation of the problem in this study was: "How does the influence of the use of Guess the Learning model of Learning Motivation for PPKn Class X Students in SMAN 1 Tualang Siak Regency?". This study aims "to determine the effect of the use of Guess the Learning model of Learning in the Learning Motivation of Class X Students in SMAN 1 Tualang Siak Regency". This research is a quantitative research that is experimental. The population in this study was class X students at SMAN 1 Tualang Siak Regency. The sample in this study was taken based on the "Random Sampling" technique. Where classes taken as samples are students of Class X Natural Science 8 (experimental class) who are given a Guess the Learning model and class X IPS 1 (control class) are students who are given the conventional method. Then the data analysis using homogeneity test, t-test and gain test. Based on the results of the study showed that there is an influence of learning motivation between students who use the Guess Learning model with conventional learning in SMAN 1 Tualang Siak Regency can be seen from the results (tcount = 29.50> ttable = 3.99). Where there is an increase in the average motivation to learn PPKn in the experimental class from 22.88 to 32.54 while the average motivation to learn PPKn in the control class from 25.32 to 25.61. With an average gain of 0.56 included in the category of "medium" Thus there is an influence of PPKn learning motivation using the Guess Learning with conventional learning model at SMAN 1 Tualang Siak Regency.Key Words: Predition Guide, Learning Motivation